SIFAT PEMESINAN BEBERAPA JENIS KAYU ASAL IRIAN JAYA - Jamal Balfas (Jurnal Penelitian Hasil Hutan, 1994)
Nine wood species collected  from  Sarong,  Iriarn Jayo,  were observed for  their machining properties.   Sawing characteristics (feed speed and surface smoothness) of each species were observed to  determine its cutting-ability. Other machining properties  (planing, shaping,  boring.  turning and sanding)  were determined according  to the modifled  ASTM D-1666 method  as  festly   described in  the  Forest  Products Research  Institute  Report  No.  160  (1982).  Planing and shaping of samples  were  observed  in wet  condition (above EMC) and again after air-drying, whereas  the remaining  properties  were  observed  only  at  air-dry condition.Results showed that most of the species couid be sawn fairly easily, and  indicaud a variation  in cutting surface qualjty, ranging from rough  to  smooth.   One species,  i.e.,   goh  (T.richadenia phiilippinensis)   was  quite difficult  to  saw for  its  irregular  (partly nterlocked) grain orientation and very  high density.   Testing of wood  samples in wet condition produced  a satisfactory planing and shaping  quality for most  wood species.  However,  testing   at   air-dry  condition  significantly revealed  a better  machining  quality. Based on the  machining characteristics  observed  on  the  nine wood species from  Sorong,  it is recommendable  to use the timbers  for  woodworking purposes.